OUTCOMES OF TOTAL LAPAROSCOPIC HYSTERECTOMY BASED ON UTERINE SIZE IN CASES OF UTERINE LEIOMYOMAS - Hameed, Nazneen; Saleem Dojki, Samina; Bano, Alia; Hameed, Mahgul; Hameed, Mehreen (Journal of Ayub Medical College Abbottabad, 2024)
Background: Uterine leiomyoma’s, also known as fibroids, are benign monoclonal tumors that originate from the soft tissue of the myometrium. Extracellular factors such as proteoglycans, fibronectin, and collagen characterized the tumors. The present study aimed to determine outcomes of total laparoscopic hysterectomy based on uterine size in uterine leiomyoma’s cases. Methods: This cross-sectional study investigated 60 uterine leiomyomas patients who underwent total laparoscopic hysterectomy in the Department of Gynecology and Endoscopic Unit of Patel Hospital, Karachi from January 2023 to December 2023. Patients were distributed based on uterine weight are as follows; Group-A (<14 weeks and <500 gms) and Group B (‰¥14 weeks and >500gms). All the patients with benign uterine pathology undergoing total laparoscopic hysterectomy were enrolled. Variable measured included age, preoperative characteristics, body mass index, and duration of surgery, blood loss, and uterine weight. SPSS version 21 was used for descriptive statistics. Results: The overall mean age, and body mass index was 45.48±4.97 years, and 27.68±3.76 kg/m2, respectively. The mean duration of surgery was 107.17±30.56 minutes. The mean duration of surgery in Group-A (n=30) and Group B (n=30) was 106.78±28.96 and 107.56±32.16 minutes, respectively. Hypertension was the most prevalent comorbidities followed by diabetes. The mean uterus size (weeks + kg) was 13.23±2.66 and 373.495±147.92. Mean total estimated blood was 73.02±32.36 ml. It has been observed that duration of surgery and uterus size was lower in Group-A than Group-B. Conclusion: The present investigation observed that total laparoscopic hysterectomy (TLH) are optimal when the uterus weighs less than 500 gms. Additionally, uterus weight <500 gms had lower body mass index, duration of surgery and blood loss as compared to uterus weight >500 gms.